2020
DOI: 10.21083/ajote.v9i0.5731
|View full text |Cite
|
Sign up to set email alerts
|

Affordances and Constraints of Implementing Lesson Study for Teachers’ Professional Development: A Review

Abstract: Lesson Study (LS) has been adopted worldwide as a research tool for teachers who teach the same subjects to cooperate in identifying problems, planning a lesson, teaching that lesson and coming up with solutions to the problem identified. This helps them grow professionally. This study is a review of approaches to implementing LS in different places, of opportunities that the use of LS provides, and of constraints on its effectiveness and sustainability. In this study, 30 published research articles were thoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Concerning to teacher educators' professional learning and development, this study showed that teacher educators' learning process occurs more during LS training (EfECT training project) than during teaching practice because some challenges such as time constraint, hinder teacher educators' professional learning through LS. The result agrees with the studies of Coe et al, 2010;Meyer &Wilkerson, 2011, cited in Kihwele andSang (2020) which proved that time is an important resource in facilitating and accomplishing the implementation of LS.…”
Section: Discussionsupporting
confidence: 92%
“…Concerning to teacher educators' professional learning and development, this study showed that teacher educators' learning process occurs more during LS training (EfECT training project) than during teaching practice because some challenges such as time constraint, hinder teacher educators' professional learning through LS. The result agrees with the studies of Coe et al, 2010;Meyer &Wilkerson, 2011, cited in Kihwele andSang (2020) which proved that time is an important resource in facilitating and accomplishing the implementation of LS.…”
Section: Discussionsupporting
confidence: 92%
“…Due to its benefits in sustaining teachers upgrading their professional competencies, some countries have emphasized implementing lesson study to help pre-service teachers learn, internalize and practice. These countries include the US, Zambia, Canada, the UK and South Africa (Kihwele & Sang, 2020). However, lesson study faces several constraints in its implementation, which hinder the achievement of expected learning outcomes among teachers.…”
Section: Lesson Study Implementation Challengesmentioning
confidence: 99%